Russian Companies Credit Default Swap Valuation Using Reduced-form and Merton models - МезенцевВ. В. (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2012)
Author: V. V. Mezentsev - National Research University "Higher School of Economics." Credit default swap is an instrument for pricing the credit risk of the company by market participants. This article discusses the application of the reduced-form model and the structural model (the Merton model) for pricing the credit default swaps on Russian companies and banks: Gazprom, Sberbank, VTB, Lukoil, Transneft and Severstal. Conclusions about the accuracy of estimates of each type of the model are made, and methods by which the predictive power of the models can be increased are provided.